Influence of Technology Adoption Interventions on Performance of Selected Commercial State Corporations in Kenya - Hawario Asser, Juliana; Waiganjo, Esther; Njeru, Agnes (Multidisciplinary Journal of Technical University of Mombasa, 2023)
Organizations all over the world strive to remain in operation through application of change management. This implies that managers who fail to adopt changes remain irrelevant in the market. The existing literature denoted gaps in the areas of technology adoption interventions as a strategic change agent in commercial state corporations in Kenya. The aim of the study was to determine the relationship between technology adoption interventions and performance of commercial state corporations in Kenya. The target was 55 commercial state corporations and a total of 48 were studied. These were obtained through stratified random sampling. The respondents of this study constituted CEOs, Finance Managers and HR Managers of each of the sampled commercial state corporations. A total of 144 respondents participated in the study through interviews using questionnaires. Regression models were fitted and hypothesis testing was carried using standard F and t tests. Technology adoption interventions was assessed by four sub-variables namely acquisition of IT infrastructure, strategic alignment, organization structure and employee training. Seven factors were subjected to factor analysis. Two factors that is, acquisition of IT and employee training were identified with the highest influence on technology adoption interventions with cumulative variance of 69.7%. Factor one had the highest with 53.2% while factor two had 16.6% of total variance. Acquisition of IT and employee training had eigen values greater than 1. Respondents on average agreed that acquisition of technology affects technology adoption interventions with a mean of 3.9449. Respondents also agreed that employee training affects technology adoption interventions with a mean of 3.8189. The results showed a strong positive and significant relationship between acquisition of technology and performance (r = 0.512; p = 0.000). The regression coefficients results of the Technology adoption interventions measures were found to be significant at 5% level of significance with a coefficient of 0.491 and p-value of 0.000. This implied that the null hypothesis was rejected and the alternative hypothesis was accepted that technology adoption interventions influenced performance of commercial state corporations in Kenya. Acquisition of technology, had a positive and linear relationship with performance. There was also a positive relationship between employee training and performance. This therefore, underscored the importance of technology acquisition and also training the agents involved in the change interventions. From the findings of this study, it can be concluded that technology adoption interventions which had acquisition of technology and employee training as sub-variables retained after factor analysis was found to have a significant relationship with performance of commercial state corporations in Kenya.